Analysis of the efficiency of social food programs and their effectiveness for poverty reduction, 2012 -2021 - Quispe Llanos, Renán (2024)
The research addresses the evaluation of the effectiveness of social food programs in Peru from 2012 to 2021. The findings indicate that the "Qali Warma" program exhibits deficiencies in budget management, since the increase in beneficiaries is attributed to the inclusion of people not qualified as poor. As for "Cuna Más", there has been a decrease in its effectiveness in recent years, mainly due to the impact of the pandemic. On the other hand, the "Vaso de Leche" program, despite receiving fewer resources, demonstrates its effectiveness in contributing to the improvement of social welfare. In contrast, the evolution of the health program has not been as successful in ensuring a significant reduction in anemia and chronic malnutrition in children. Logistic regression analysis reveals that these programs are preferentially implemented in urban areas and are not necessarily associated with family per capita income, except in the case of the "Cuna Más" program.